THE STUDY OF WOOD-CEMENT BONDING BY THE STICK TEST METHOD - Jirayut, Tawat (วารสารวนศาสตร์ไทย, 2022)
The preliminary study on wood-cement bonding by the stick test method was carried out by investigating the compatibility of 13 timber species with Diamond-brand portland cement, which is available on the domestic market. Based on the results, the method provided a quick sorting of the suitable species for making the wood-cement products. There is still no better way to assess the overall suitability of a species than to produce the products and to test them.